Surgical therapy in advanced sinonasal carcinomas - retrospective study - Hrabalek, Lumir; Novak, Vlastimil; Hoza, Jiri; Hucko, Csaba; Vaverka, Miroslav; Krahulik, David; Pohlodek, Daniel (Biomedical papers, 2024)
Background and Aim. Sinonasal tumors are a rare and heterogeneous group of malignant tumors with different histopathological characteristics and clinical presentation. These tumors are usually treated through surgery. The aim of this study is to present our results of surgical therapy in patients with an advanced sinonasal tumor.Methods. This retrospective study included patients with an advanced sinonasal tumor who were surgically treated. The surgical technique combined both a frontal transbasal approach together with an endoscopic endonasal approach. The parameters used for evaluation were the histological type of tumor, the radicality of resection (complete vs. incomplete), the frequency of recurrence, the surgical and postoperative complications, the type of subsequent oncological therapy and the overall survival.Results. The group consisted of ten patients seven were men and three were women. Complete resection (defined as R0) was achieved in 8 (80%) of the cases, subcomplete resection was achieved in 2 (20%) of the cases. The overall survival period was 28.7 months (95% confidence interval 15.9-41.6).Conclusion. The combination of the frontal transbasal approach with the endoscopic endonasal approach is a suitable surgical strategy that enables easier achievement of complete tumor resection, reconstruction of the anterior skull base and reduces the need for extensive surgical approaches.
Keywords: sinonasal tumors; transbasal approach; endoscopic surgery; skull base